2015
DOI: 10.1021/acs.jproteome.5b00125
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics Reveals Metabolite Changes in Biliary Atresia Infants

Abstract: Biliary atresia (BA) is a rare neonatal cholestatic disorder caused by obstruction of extra and intra hepatic bile ducts. If untreated, progressive liver cirrhosis will lead to death within two years. Early diagnosis and operation improve the outcome significantly. Infants with neonatal hepatitis syndrome (NHS) present similar symptoms, confounding the early diagnosis of BA. The lack of non-invasive diagnostic methods to differentiate BA from NHS greatly delays the surgery of BA infants, thus deteriorating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…This abnormal increase in AST accelerated lysine consumption and produced oxaloacetic acid. Lysine is an essential amino acid, and elevated L-lysine levels in the plasma have been reported in both ICH and EHBA, which is consistent with our results 29 , 46 . Decreased concentrations of carnitine were also detected in the plasma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This abnormal increase in AST accelerated lysine consumption and produced oxaloacetic acid. Lysine is an essential amino acid, and elevated L-lysine levels in the plasma have been reported in both ICH and EHBA, which is consistent with our results 29 , 46 . Decreased concentrations of carnitine were also detected in the plasma.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a metabolic disorder of glutamine and glutamate pathway was reported in carbon tetrachloride induced acute hepatotoxicity and in patients with jaundice syndrome 27 , 28 . Notably, plasma glutamate levels in infants with EHBA were reported to be significantly higher than those in infants with ICH, which is consistent with the result of our study 29 . However,whether the glutamine and glutamate disorder was caused by HCMV infection or hepatocellular injury remains unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Much effort has been made to search for new BA biomarkers. Our previous study found plasma metabolic profiling had great potential in differentiating BA from NHS, and amino acid metabolism was significantly different between the two diseases . Circulating levels of the miR-200b/429 cluster were found elevated in BA infants compared to cholestatic controls.…”
Section: Discussionmentioning
confidence: 91%
“…The metabolites were then derivatized for detection by GC-MS. Methoxyamine hydrochloride solution (100 μL of 20 mg mL −1 in pyridine, Sigma-Aldrich) was added to the extracted metabolites, and methoxyamination proceeded for 90 min at 37 °C. Subsequently, the same volume of BSTFA solution (N,O-bis(trimethylsilyl)trifluoroacetamide with 1% trimethylchlorosilane, Sigma-Aldrich) was used for trimethylsilylation during derivatization for 25 min at 50 °C3839. The derivatized samples were analyzed using a GCMS-2010 plus (Shimadzu, Japan) equipped with a DB-5 capillary column (30 m × 0.25 mm, 0.25 μm thickness, Agilent, USA).…”
Section: Methodsmentioning
confidence: 99%